2017
DOI: 10.3390/polym10010014
|View full text |Cite
|
Sign up to set email alerts
|

PLMA-b-POEGMA Amphiphilic Block Copolymers as Nanocarriers for the Encapsulation of Magnetic Nanoparticles and Indomethacin

Abstract: Abstract:We report here on the utilization of poly(lauryl methacrylate)-b-poly(oligo ethylene glycol methacrylate) (PLMA-b-POEGMA) amphiphilic block copolymers, which form compound micelles in aqueous solutions, as nanocarriers for the encapsulation of either magnetic iron oxide nanoparticles or iron oxide nanoparticles, and the model hydrophobic drug indomethacin in the their hydrophobic core. The mixed nanostructures were characterized using dynamic light scattering (DLS) and transmission electron microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…There are many studies in this field that confirm the potential and function of the micellar structures for anticancer drug delivery 29–31 . In this regard, some monomers such as HEMA (2‐hydroxyethyl methacrylate), LMA (lauryl methacrylate), MMA (Methyl methacrylate), BMA (n‐butyl methacrylate), and OEGMA (Oligo ethylene glycol methyl ether methacrylate) can be suitable options for the synthesis of AmBCs due to hydrophilic/hydrophobic and biocompatible characters which are resulted from their side chains 24,32–34 …”
Section: Introductionmentioning
confidence: 96%
“…There are many studies in this field that confirm the potential and function of the micellar structures for anticancer drug delivery 29–31 . In this regard, some monomers such as HEMA (2‐hydroxyethyl methacrylate), LMA (lauryl methacrylate), MMA (Methyl methacrylate), BMA (n‐butyl methacrylate), and OEGMA (Oligo ethylene glycol methyl ether methacrylate) can be suitable options for the synthesis of AmBCs due to hydrophilic/hydrophobic and biocompatible characters which are resulted from their side chains 24,32–34 …”
Section: Introductionmentioning
confidence: 96%
“…Therefore, they are being extensively developed and constructed due to their multi-functionality for the cure of various life-threatening diseases. A wide range of research has been reported to procure the effectiveness of such materials in theranostic applications [1][2][3][4][5][6][7][8][9]. Polymer nanomedicine is based on the development of copolymers that are biodegradable and biocompatible, and provides bioavailability and colloidal stability to the formed multifunctional hybrid nanomaterials and entrapped species.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic nanoparticles (MNPs) have been used in a multitude of biomedical applications including magnetic resonance imaging (as negative contrast agents), gene therapy, targeted drug delivery, and magnetic hyperthermia treatment (under alternating magnetic fields) [ 22 , 23 , 24 , 25 , 26 ], rendering them ideal for the design of hybrid nanostructures based on polymers.…”
Section: Introductionmentioning
confidence: 99%